Genetic associations between autoimmune diseases and the risks of severe sepsis and 28-day mortality: a two-sample Mendelian randomization study - Tie, Xin; Zhao, Yanjie; Su, Jing; Liu, Xing; Zou, Tongjuan; Yin, Wanhong (Frontiers in Medicine, 2024)
Background: Certain aAutoimmune diseases exhibit heterogenous dysregulation of pro-inflammatory or anti-inflammatory cytokine expression, akin to the pathophysiology of sepsis. It is speculated that individuals with autoimmune diseases may have an increased likelihood of developing sepsis and face elevated mortality risks following septic events. However, current observational studies have not yielded consistent conclusions. This study aims to explore the causal relationship between autoimmune diseases and the risks of sepsis and mortality using Mendelian randomization (MR) analysis.Methods: We conducted a two-sample MR study involving a European population, with 30 autoimmune diseases as the exposure factors. To assess causal relationships, we employed the inverse variance-weighted (IVW) method and used Cochran's Q test for heterogeneity, as well as the MR pleiotropy residual sum and outlier (MR-PRESSO) global test for potential horizontal pleiotropy.Results: Genetically predicted Crohn's disease (β=0.067, se=0.034, p=0.046, OR=1.069, 95% CI=1.001-1.141) and idiopathic thrombocytopenic (β=0.069, se=0.031, p=0.023, OR=1.071, 95% CI=1.009-1.136) were positively associated with an increased risk of sepsis in critical care. Conversely, rheumatoid arthritis (β=-0.104, se=0.047, p=0.025, OR=0.901, 95% CI=0.823-0.987), ulcerative colitis (β=-0.208, se=0.084, p=0.013, OR=0.812, 95% CI=0.690-0.957), and narcolepsy (β=-0.202, se=0.092, p=0.028, OR=0.818, 95% CI=0.684-0.978) were associated with a reduced risk of sepsis in critical care. Moreover, Crohn's disease (β=0.234, se=0.067, p=0.001, OR=1.263, 95% CI=1.108-1.440) and idiopathic thrombocytopenic (β=0.158, se=0.061, p=0.009, OR=1.171, 95% CI=1.041-1.317) were also linked to an increased risk of 28-day mortality of sepsis in critical care. In contrast, multiple sclerosis (β=-0.261, se=0.112, p=0.020, OR=0.771, 95% CI= 0.619-0.960) and narcolepsy (β=-0.536, se=0.184, p=0.003, OR=0.585, 95% CI=0.408-0.838) were linked to a decreased risk of 28-day mortality of sepsis in critical care.Conclusion: This MR study identified causal associations between certain autoimmune diseases and risks of sepsis in critical care, and 28-day mortality in the European population. These findings suggest that exploring the mechanisms underlying autoimmune diseases may offer new diagnostic and therapeutic strategies for sepsis prevention and treatment.